Plant-derived compounds as a tool for the control of gastrointestinal nematodes: Modulation of abamectin pharmacological action by carvone - Miró, María Victoria (2020)
The combination of synthetic anthelmintics and bioactive phytochemicals may be a pharmacological tool for improving nematode control in livestock. Carvone (R-CNE) has shown in vitro activity against gastrointestinal nematodes; however, the anthelmintic effect of bioactive phytochemicals either alone or combined with synthetic drugs has been little explored in vivo. Here, the pharmacological interaction of abamectin (ABM) and R-CNE was assessed in vitro and in vivo. The efficacy of this combination was evaluated in lambs naturally infected with resistant gastrointestinal nematodes. Additionally, the ligand and molecular docking of both molecules to P-glycoprotein (P-gp) was studied in silico. The presence of R-CNE produced a significant (p < 0.05) increase of Rho123 and ABM accumulation in the intestinal explants. After 60 min of incubation, Rho123 incubated with R-CNE had a 67 ± 21% higher concentration (p < 0.01) than when it was incubated alone. In the case of ABM, a significant increase in the intestinal concentrations was observed at 15 and 30 min after incubation with R-CNE. In the in vivo assay, no undesirable effects were observed after the oral administration of R-CNE. The coadministration of the natural compound prolonged ABM absorption in lambs. ABM T½ absorption was 1.57-fold longer (p < 0.05) in the coadministered group. Concentrations of R-CNE between 420 and 2,593 ng/mL were detected in the bloodstream between 1 and 48 h posttreatment. The in vivo efficacy of ABM against gastrointestinal nematodes increased from 94.9 to 99.8% in the presence of R-CNE, with the lower confidence interval limit being >90%. In vitro/in vivo pharmacoparasitological studies are relevant for the knowledge of the interactions and the efficacy of bioactive natural products combined with synthetic anthelmintics. While ADMET (absorption, distribution, metabolism, excretion, and toxicity) predictions and the molecular docking study showed a good interaction between ABM and P-gp, R-CNE does not appear to modulate this efflux protein. Therefore, the pharmacokinetic–pharmacodynamic effect of R-CNE on ABM should be attributed to its effect on membrane permeability. The development of pharmacology-based information is critical for the design of successful strategies for the parasite control.